Explicating the publication paradigm by bibliometric approaches: A case of interplay between nanoscience and ferroptosis - Zhengwei Huang; Wenhao Wang; Lei Shu; Mengqin Guo; Ying Huang; Chuanbin Wu; Xin Pan (Wiley, 2022)
Abstract Background Ferroptosis has been widely investigated as an emerging drug target, while its combination with nanoscience provides bourgeoning application prospects. The development of ferroptosis regulating nanomedicines have attracted worldwide attentions in recent years. It would be meaningful to describe the relevant publication paradigm. Methods Herein, a bibliometric analysis was performed using the database of Web of Science Core Collection to clarify the publication paradigm. The development of related publications in the last 6 years was described, and the revolutionary trends were figured out. Ultimately, the possible future exploration directions were proposed. Results The bibliometric analysis of 327 documents of interest indicated that the main research focus was in multiple fields including Materials science, Science & technology, Chemistry, and Pharmacology & pharmacy. With widely cooperation and strong funding, the researchers from Chinese organizations contributed most of publications, followed with United States and Australia. Cocitation analysis revealed that several original papers reported the key molecular mechanisms of ferroptosis were considered as the foundation for subsequent studies, and some nanomedicines‐related documents were taken as examples and discussed. Mining results showed that the mechanism evaluation of ferroptosis regulation therapy for cancer treatment was the hotspot. Then, several possible future explorations of ferroptosis‐related nanoscience were presented and discussed. Conclusions The bibliometric profile of nanoscience‐ferroptosis research was analyzed in detail. We believe that the bibliometric analysis could act as a robust method for explicating the publication paradigm as a certain field.